Konflik antar-lembaga di Pedesaan (Penelitian di Kanagarian Pianggu Sumatera Barat) - S, Nurman (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2002)
This research aimed to identify the source of conflict that occurred in authorizing Nagari Market. This research was conducted in Kenagarian Pianggu, Subdistrict of IX Koto Sungai Lasi, Regency of Solok through a qualitative method. Data is collected through depth interview technique and direct observation and supported by library studies. Sampling used is snowball sampling, whereas data analysis is conducted by using triangulation. The findings of research indicate that there are four causal source of conflict on authorizing Nagari Market between village government and KAN, that is: (1) a different and controversy of value that followed by the village government and KAN; (2) overlapping of power and authority that possessed by the village government and KAN; (3) economical interest of the two institutions; and (4) the implementation of more high government policy, that is Undang-undang No.5/1979, in West Sumatra. Key Words: conflict, village government, Kerapatan Adat Nagari (KAN)